Tailoring the Optical Parameters of Optical Fiber Interferometer With Dedicated Boron‐Doped Nanocrystalline Diamond Thin Film (Phys. Status Solidi A 11∕2017). Issue 11 (13th November 2017) - Majchrowicz, Daria; Kosowska, Monika; Struk, Przemysław; Jędrzejewska‐Szczerska, Małgorzata
Abstract : Researchers from the Gdańsk University of Technology in Poland (article No.201700222 ) have developed an optical fiber interferometer in Fabry‐Perot configuration with a borondoped diamond reflective layer as a mirror. The experimental set‐up consists of a light source, fiber optic coupler, optical fiber links, optical spectrum analyzer and the measurement head. The quality of the layer was examined by scanning electron microscopy (SEM), atomic force microscopy (AFM) and Raman spectroscopy. The use of boron‐doped diamond layer provided a very high value of signal visibility, reduction of cavity length and possibility of measuring aggressive substances